Pengaruh Model Pembelajaran STEM terhadap Kemampuan Literasi Sains Siswa Sekolah Dasar - Fikriya, Nanda; Hidayat, Otib Satibi; Hasanah, Uswatun (Kompetensi : Jurnal Pendidikan dan Humaniora Fakultas Keguruan dan Ilmu Pendidikan UNIBA, 2023)
This study aims to determine the effect of STEM learning on scientific literacy skills in fifth grade students at SDN Cipinang Besar Utara 03. This study used an experimental method with a one group pretest posttest design. The sample used in this study was fifth grade students, totaling 21 people. The instrument used in this study was a written test in the form of multiple choice questions. Based on the results of statistical data processing using the Wilcoxon Test, the results of Ha are accepted because Tcount (0) < Ttable (59) which means that there is a significant influence on increasing students' scientific literacy using the STEM learning model.